SPRINT: A Tool to Generate Concurrent Transaction-Level Models from Sequential Code. (30th April 2007) - Cockx Cockx, Johan Johan; Denolf Denolf, Kristof Kristof; Vanhoof Vanhoof, Bart Bart; Stahl Stahl, Richard Richard
Abstract : A high-level concurrent model such as a SystemC transaction-level model can provide early feedback during the exploration of implementation alternatives for state-of-the-art signal processing applications like video codecs on a multiprocessor platform. However, the creation of such a model starting from sequential code is a time-consuming and error-prone task. It is typically done only once, if at all, for a given design. This lack of exploration of the design space often leads to a suboptimal implementation. To support our systematic C-based design flow, we have developed a tool to generate a concurrent SystemC transaction-level model for user-selected task boundaries. Using this tool, different parallelization alternatives have been evaluated during the design of an MPEG-4 simple profile encoder and an embedded zero-tree coder. Generation plus evaluation of an alternative was possible in less than six minutes. This is fast enough to allow extensive exploration of the design space.